2022
DOI: 10.3390/toxins14080517
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Fungal Phytotoxins on Cancer Cell Viability: First Insight into Structure Activity Relationship of a Potent Metabolite of Cochliobolus australiensis Radicinin

Abstract: Natural compounds have always represented an important source for new drugs. Although fungi represent one such viable source, to date, no fungal metabolite has been marketed as an anticancer drug. Based on our work with phytotoxins as potential chemical scaffolds and our recent findings involving three phytopathogenic fungi, i.e., Cochliobolus australiensis, Kalmusia variispora and Hymenoscyphus fraxineus, herein, we evaluate the in vitro anti-cancer activity of the metabolites of these fungi by MTT assays on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…can inhibit the proliferation and migration of tumor cells by inducing apoptosis and autophagy, offering a promising strategy for cancer therapy [ 122 , 123 ]. To fully evaluate the potential of fungal metabolites as anticancer agents, a combination of in vitro and in vivo studies is necessary [ 40 , [124] , [125] , [126] ]. Molecular docking techniques can also be employed to predict the potential binding modes and affinity of these compounds to their target proteins [ 79 , 82 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…can inhibit the proliferation and migration of tumor cells by inducing apoptosis and autophagy, offering a promising strategy for cancer therapy [ 122 , 123 ]. To fully evaluate the potential of fungal metabolites as anticancer agents, a combination of in vitro and in vivo studies is necessary [ 40 , [124] , [125] , [126] ]. Molecular docking techniques can also be employed to predict the potential binding modes and affinity of these compounds to their target proteins [ 79 , 82 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 ), which is the immediate biosynthetic precursor of radicinin ( 10 ) [ 36 ] was realized and aimed to determine the role of the hydroxygroup at C-3 and its absolute configuration to impart phytotoxicity [ 37 ]. The results of (±)-3-deoxyradicinin ( 25 ) assay, suggested that the stereochemistry of C-3 seemed to have some role, because 3- epi -radicinin was less active [ 38 ]. Successively, radicinin ( 10 ) was tested for its anticancer activity towards three human cancer cell lines such as A549 NSCLC (DSMZ code ACC107), Hs683 oligodendroglioma (ATCC code HTB-138) and SKMEL-28 melanoma (ATCC code HTB-72) cells, and showed a promising toxicity (IC 50 values of 7.7 ± 0.6, 8.7 ± 0.4, 8.2 ± 0.2 μM).…”
Section: Metabolites From Terrestrial Fungimentioning
confidence: 99%
“…The activities of (±)-3-deoxy- and 2,3-dehydroradicinin ( 25 and 26 ) were slightly lesser than that of radicinin ( 10 ), demonstrating that the 3-hydroxy group plays a minor role in the activity. Among the synthetic intermediates only the methoxypyrones showed moderate anticancer activities [ 38 ]. The results of this SAR study are in good agreement with those obtained testing the phytotoxic activity against the host plant and other infestant plants also using other natural analogues of 10 [ 35 ].…”
Section: Metabolites From Terrestrial Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…From a biological point of view, radicinin is an interesting metabolite, having several biological effects, including promising herbicidal effects [5,[10][11][12] and antifungal, insecticidal, and plant growth regulatory activities [13][14][15][16], as well as antibiotic activity against Gram-positive bacteria [17]. More recently, the toxin was shown to possess in vitro anticancer activity [18]. However, despite its interesting biological properties and its potential as a natural herbicide, the modest amounts obtainable by fungal fermentation constitute a bottleneck for scientific investigations or applicative developments.…”
Section: Introductionmentioning
confidence: 99%